ANALYSIS OF LEADERSHIP STYLE AND WORK DISCIPLINE ON TEACHER PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT AT STATE VOCATIONAL SCHOOL 2 BENER MERIAH - Ruhdi Muharram Selian; Kiki Farida Ferine; Mesra B (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research investigates the influence of leadership style and work discipline on teacher performance through organizational commitment at State Vocational School 2 Bener Meriah. A quantitative research method was employed, using a saturated sample of 63 teachers. Data was collected through questionnaires and analyzed using SmartPLS. The findings indicate that leadership style has a positive, but not significant, effect on teacher performance, while work discipline has a positive and significant effect. Both leadership style and work discipline positively and significantly influence organizational commitment, which in turn positively and significantly affects teacher performance. Organizational commitment also mediates the relationship between leadership style, work discipline, and teacher performance. The study suggests that schools should focus on improving leadership, work discipline, and organizational commitment to enhance teacher performance.